Mazu belief and happiness: a sequential mediation model involving mental health and positive emotions among Taiwanese followers - Chang, Hsiao-Ming; Lin, Ching-Hui (Frontiers in Psychology, 2025)
IntroductionThis study explores the psychological impact of Mazu beliefs on the happiness of Taiwanese followers, emphasizing the sequential mediating roles of mental health and positive emotions. Given the cultural prominence of Mazu belief in Taiwan, this research sheds light on its potential contributions to enhancing well-being from the perspective of positive psychology.MethodsUsing a questionnaire survey, convenience sampling was employed to collect data from followers at 57 Mazu temples across 20 counties and cities in Taiwan. A total of 402 valid responses were obtained. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among Mazu beliefs, mental health, positive emotions, and happiness.ResultsThe analysis demonstrated that Mazu beliefs positively and significantly influence mental health and positive emotions. Additionally, Mazu beliefs were found to affect happiness indirectly through the sequential mediation of mental health and positive emotions. These findings support the theoretical framework linking religious belief to emotional and psychological well-being.DiscussionThis study highlights the critical role of culturally embedded religious practices, particularly Mazu beliefs, in fostering mental health and enhancing positive emotions, which collectively promote happiness among followers. These results contribute to advancing the understanding of the intersection between Eastern religious beliefs and positive psychology, offering insights into how spiritual practices can sustain emotional resilience and psychological well-being.